Modified Diffusion Tensor Image Processing Pipeline for Archived Studies of Patients With Leukoencephalopathy. Issue 3 (15th April 2021) - Song, Ruitian; Glass, John O.; Reddick, Wilburn E.
Abstract : Background: In archived diffusion tensor imaging (DTI) studies, a reversed‐phase encoding (PE) scan required to correct the distortion in single‐shot echo‐planar imaging (EPI) may not have been acquired. Furthermore, DTI tractography is adversely affected by incorrect white matter segmentation due to leukoencephalopathy (LE). All these issues need to be addressed. Purpose: To propose and evaluate a modified DTI processing pipeline with DIstortion COrrection using pseudo T2 ‐weighted images (DICOT) to overcome limitations in existing acquisition protocols. Study Type: Retrospective feasibility. Subjects: DICOT was assessed in simulated data and 84 acute lymphoblastic leukemia (ALL) patients with reversed PE acquired. The pipeline was then tested in 522 scans from 261 ALL patients without a reversed PE acquired. Field Strength/Sequence: A 3 T; diffusion‐weighted EPI; 3D magnetization prepared rapid acquisition gradient echo (MPRAGE). Statistical Tests: Repeated measures analysis of variance and Tukey post hoc tests were performed to compare fractional anisotropy (FA) values obtained by different methods. Assessment: FA and corresponding absolute error maps were obtained using TOPUP, DICOT, INVERSION (Inverse contrast Normalization for VERy Simple registratION) and NO CORR (no correction). Each method was assessed by comparing to TOPUP. The pipeline in the ALL patients was evaluated based on the failure rate of the distortion correction using the global correlation values. Results: Using DICOT reduced the mean absolute errors by an average of 32% in FA in simulation datasets. In 84 patients, the error reductions were approximately 15% in FA with DICOT, while it was 5% with INVERSION. No significant differences between the TOPUP and DICOT were observed in FA with P  = 0.090/0.894(AP/PA). Only 15 of 516 examinations requiring any additional manual intervention. Conclusion: This modified pipeline produced better results than the INVERSION. Furthermore, robust performance was demonstrated in archived patient scans acquired without an inverse PE necessary for TOPUP correction. Evidence Level: 3 Technical Efficacy: Stage 2